Guardians at the Gate: Early Adversity, Neurocognitive Development, and the Role of the Pediatrician in the Era of COVID-19 - Berken, Jonathan A.; Heard-Garris, Nia; Wakschlag, Lauren S. (Frontiers in Pediatrics, 2021)
Adverse childhood experiences (ACEs) profoundly impact neurocognitive development. Specifically, when these events occur during critical periods of brain plasticity, a time of significant synaptogenesis, neural pruning, and myelination, typical neurodevelopment can become derailed. ACEs promote morphological changes in neuronal microcircuitry which may lead to diminished cognitive flexibility, inattention, increased impulsivity, decreased school readiness and disruptive behaviors. In this regard, the current COVID-19 pandemic represents an especially complex adverse experience that disturbs a child’s social milieu and support network, likely interfering with brain maturation and executive function. Here, we take a neurodevelopmental approach to argue for the critical role that pediatricians must fulfill in mitigating the potentially detrimental consequences of COVID-19. We call for ACE screening and anticipatory guidance in the primary care setting, and the use of validated interventions and skills to bolster resilience, when ACEs are identified. We present a clinical workflow for the physician to proactively assess, identify, stratify, and address the severity of adverse childhood experiences worsened by COVID-19. We discuss home-based activities and resources for children and adolescents to promote stress reduction, connectiveness, and self-awareness and create a more positive environment to maximize neurodevelopmental potential in the face of the ongoing pandemic.